STOP BULLYING DENGAN MENINGKATKAN KETERAMPILAN SOSIAL PADA SISWA SMP METHODIST 1 MEDAN - Saputra, Yoza Okta; Josetta Maria Remila Tuapattinaja; Eka Danta Jaya Ginting; Rahma Fauzia (Jendela Akademika, 2024)
Education is a place for producing students who are intelligent, disciplined, independent, and of high quality. Schools should be safe and comfortable places for learning; however, recently they have become environments where bullying cases are developing. SMP Methodist 1 has become one of the schools where bullying occurs. Bullying is a form of behavior that harms others who are perceived as weak, economically disadvantaged, or disabled. Bullying can be physical, such as hitting and other aggressive actions carried out individually or in groups. Verbal bullying is also common and includes mocking physical appearance, financial status, belittling peers or parents, using inappropriate language, and intimidation. Additionally, there is cyberbullying, which is conducted by individuals or groups through social media to ostracize others. Bullying has dangerous and long-lasting consequences, affecting physical, emotional, and mental health, including depression, anxiety, substance abuse, and decreased academic performance. Based on this data, there is a need for effective measures to reduce bullying at SMP Methodist 1. One approach is to teach social skills. The social skills taught include empathy, communication, emotional regulation, and problem-solving. These social skills are expected to be beneficial in detecting and preventing bullying in the school.